Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT PLN (Persero) UPDK Mahakam Samarinda - Tandi Kadang; Gunadi Gunadi (Politeknik Negeri Samarinda, 2020)
The Effect of Job Training and Work Discipline on Employee Performance at PT PLN (Persero) UPDK Mahakam, This research was conducted to determine the effect of job training and work discipline at PT PLN (Persero) UPDK Mahakam. The population involved in this study were employees of PT PLN (Persero) UPDK Mahakamwho attended training with a total of 40 respondents. This research is quantitative research. The analytical tool used is using the SPSS version 17 application. For the independent variable (variabel X) of this study is job training and work discipline, while for the dependent variable (variable Y) is employee performance.